Effect of teachers’ teaching strategies on students’ learning engagement: moderated mediation model - Zhang, Heping; Yang, Junjie; Liu, Zhiyuan (Frontiers in Psychology, 2024)
Introduction This study explores the nuanced relationship between teachers’ teaching strategies and students’ learning engagement within online environments, considering the mediation by students’ perceptions of teachers’ emotional engagement and the moderation by teachers’ expectations. Methods Employing a stratified sampling technique, data were collected from 1,200 Chinese primary and secondary students through the “Survey on Online Learning Engagement.” Structural equation modeling was applied to analyze the relationships among teaching strategies, emotional engagement, teachers’ expectations, and learning engagement. Results The study found that teachers’ teaching strategies not only directly affect students’ learning engagement (r = 0.377***, p < 0.001), but also indirectly affect students’ learning engagement through students’ perception of teachers’ emotional engagement. It showed a significant mediating effect (indirect effect = 0.231***, p < 0.001). Additionally, teachers’ expectations exhibit a notable moderating effect on the relationship between perceived emotional engagement and learning engagement (β = 0.073***, p < 0.001). In other words, in addition to teachers’ teaching strategies, teachers’ emotional involvement and students’ perception of teachers’ emotional involvement are important factors affecting students’ learning involvement. This means that in online classroom teaching, the emotional transmission and experience between teachers and students play a role in the connection. Discussion The study highlights the critical role of emotional connection in educational strategies, suggesting that teachers should focus on fostering emotional engagement alongside academic content. Balanced teacher expectations are recommended to facilitate a supportive learning environment that encourages higher levels of student engagement. Educators are advised to integrate emotional warmth and responsiveness into their teaching methods and to maintain realistic expectations to promote optimal learning outcomes.